2016
DOI: 10.1371/journal.pone.0150194
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of “Brilliant” and “Genius” in Teaching Evaluations Predicts the Representation of Women and African Americans across Fields

Abstract: Women and African Americans—groups targeted by negative stereotypes about their intellectual abilities—may be underrepresented in careers that prize brilliance and genius. A recent nationwide survey of academics provided initial support for this possibility. Fields whose practitioners believed that natural talent is crucial for success had fewer female and African American PhDs. The present study seeks to replicate this initial finding with a different, and arguably more naturalistic, measure of the extent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
148
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(152 citation statements)
references
References 41 publications
2
148
1
1
Order By: Relevance
“…Analyzing Ph.D. students, they found that when a field places a higher emphasis on "brilliance," the ratio of women to men in that field tends to be lower. These results were also supported at the undergraduate level in a follow-up study (Storage et al 2016). Storage et al (2016) set out to analyze whether the frequency of the words "brilliant" and "genius" in student teaching evaluations within STEM disciplines would be related to the number of female Ph.Ds.…”
Section: Brilliance Emphasismentioning
confidence: 75%
See 2 more Smart Citations
“…Analyzing Ph.D. students, they found that when a field places a higher emphasis on "brilliance," the ratio of women to men in that field tends to be lower. These results were also supported at the undergraduate level in a follow-up study (Storage et al 2016). Storage et al (2016) set out to analyze whether the frequency of the words "brilliant" and "genius" in student teaching evaluations within STEM disciplines would be related to the number of female Ph.Ds.…”
Section: Brilliance Emphasismentioning
confidence: 75%
“…These results were also supported at the undergraduate level in a follow-up study (Storage et al 2016). Storage et al (2016) set out to analyze whether the frequency of the words "brilliant" and "genius" in student teaching evaluations within STEM disciplines would be related to the number of female Ph.Ds. and undergraduate students within a given STEM discipline.…”
Section: Brilliance Emphasismentioning
confidence: 75%
See 1 more Smart Citation
“…Effective mentoring can be difficult to measure as it involves both metrics of graduate student success (e.g., publishing papers, progress toward graduation), and less tangible metrics such as student mental health, support, and satisfaction. Additionally, evidence from research on teaching evaluations suggests that students can be biased when evaluating certain groups, such as women, and thus evaluations based on student opinion alone must be used with caution (Boring, ; Mengel, Zölitz, & Mengel, ; Miles & House, ; Stark & Freishtat, ; Storage, Horne, Cimpian, & Leslie, ). Finally, finding mechanisms that allow for honest feedback in academia is challenging, as graduate students and postdocs must be protected from retribution in cases of a negative review.…”
Section: The Way Forward: a Model For Improving Mentorship In Stemmentioning
confidence: 99%
“…Some of these stereotypes entail particular social identities-for example, that scientists are male, White, and of relatively high socioeconomic status (Archer et al, 2012(Archer et al, , 2013Barman, 1999;Buldu, 2006;Chambers, 1983;Finson, 2002;Fort & Varney, 1989;Wong, 2015). These various stereotypes also interact with one another-as when children (Bian, Leslie, & Cimpian, 2017) and adults Storage, Horne, Cimpian, & Leslie, 2016) expect those who are brilliant to also be White and male. These various stereotypes also interact with one another-as when children (Bian, Leslie, & Cimpian, 2017) and adults Storage, Horne, Cimpian, & Leslie, 2016) expect those who are brilliant to also be White and male.…”
mentioning
confidence: 99%